SHAPING SOCIAL CONSCIOUSNESS THROUGH INTERNET JOURNALISM - Tokhirova Sevinch Akram kizi (INTERNATIONAL JOURNAL OF SCIENCE-INNOVATIVE RESEARCH, 2025)
Abstract: Internet journalism has become a powerful tool in shaping social consciousness by influencing public opinion, raising awareness on social issues, and fostering civic engagement. The accessibility and immediacy of online media enable widespread dissemination of information and diverse perspectives, helping society to reflect on critical topics such as human rights, environmental protection, and social justice. This article explores the role of internet journalism in forming social awareness, its opportunities for empowerment, and challenges including misinformation and ethical concerns.